Proliferation of Small Arms, Light Weapons and Nigerian Security: A Case Study of North-Eastern Nigeria - Isah, Benjamin; Luka, Baiyi Viniru; Philip, Umar (Kashere Journal of Politics and International Relations, 2024)
Using the North-East as a case study, this research examined the impact of the proliferation of small arms and light weapons on Nigerian security. The research gathered it data from both primary and secondary sources. Content analysis was used in analyzing the data obtained for this study. According to the study, there is a growing market for small arms and light weapons (SALW) in Nigeria. The government should act more forcefully to stop this negative trend, as the spread of small arms and light weapons poses a serious threat to global transnational organized crime and undermines security and development. The fact that many security services had repeatedly found, recovered, and seized a cache of weapons and ammunition supported this claim even more. In light of these difficulties, the size of the country’s borders highlights the necessity for a reconsideration of the management and security, Protecting the country’s borders and seaports - without which an effective check or battle against the proliferation and trafficking of armaments would remain a mirage. Although it is challenging to estimate the number of illegal SALW in Nigeria, there are a sizable number of these weapons in circulation. Seizures appear to grow in proportion to an overall increase in insecurity.